Immunization With a Combination of Four Recombinant Brucella abortus Proteins Omp16, Omp19, Omp28, and L7/L12 Induces T Helper 1 Immune Response Against Virulent B. abortus 544 Infection in BALB/c Mice - Huy, Tran Xuan Ngoc; Nguyen, Trang Thi; Reyes, Alisha Wehdnesday Bernardo; Vu, Son Hai; Min, WonGi; Lee, Hu Jang; Lee, John Hwa; Kim, Suk (Frontiers in Veterinary Science, 2021)
Protective efficiency of a combination of four recombinant Brucella abortus (B. abortus) proteins, namely outer membrane protein (Omp) 16, Omp19, Omp28 and 50S ribosomal protein L7/L12 was evaluated as a combined subunit vaccine (CSV) against B. abortus infection in RAW 264.7 cell line and murine model. The immunoreactivity of these four recombinant proteins as well as pCold-TF vector reacted with Brucella¬-positive serum individually, but not with Brucella¬-negative serum by immunoblotting assay. CSV-treated RAW 264.7 cells significantly induced production of IFN-γ and IL-12 while decreased IL-10 production at the late stage of infection compared to PBS-treated control cells. In addition, the enhancement of nitric oxide production together with cytokines secretion profile in CSV-treated cells proved that CSV notably activated bactericidal mechanisms in macrophages. Consistently, mice immunized with CSV strongly elicited production of pro-inflammatory cytokines TNF-α, IL-6 and MCP-1 compared to PBS control group. Moreover, the concentration of IFN-γ was greater than IL-10 and titers of IgG2a were also heightened compared to IgG1 in CSV-immunized mice which suggest that CSV induced predominantly T helper 1 T cell. These results suggest that the CSV used in the present study is a potential candidate as a preventive therapy against brucellosis.